The Action of the Hexokinase Inhibitor 2‐deoxy‐d‐glucose on Cryptosporidium parvum and the Discovery of Activities against the Parasite Hexokinase from Marketed Drugs. (5th October 2018) - Eltahan, Rana; Guo, Fengguang; Zhang, Haili; Zhu, Guan
Abstract: Cryptosporidium parvum is one of the major species causing mild to severe cryptosporidiosis in humans and animals. We have previously observed that 2‐deoxy‐d ‐glucose (2DG) could inhibit both the enzyme activity of C. parvum hexokinase (CpHK) and the parasite growth in vitro. However, the action and fate of 2DG in C. parvum was not fully investigated. In the present study, we showed that, although 2DG could be phosphorylated by CpHK to form 2DG‐6‐phosphate (2DG6P), the anti‐cryptosporidial activity of 2DG was mainly attributed to the action of 2DG on CpHK, rather than the action of 2DG or 2DG6P on the downstream enzyme glucose‐6‐phosphate isomerase (CpGPI) nor 2DG6P on CpHK. These observations further supported the hypothesis that CpHK could serve as a drug target in the parasite. We also screened 1, 200 small molecules consisting of marketed drugs against CpHK, from which four drugs were identified as CpHK inhibitors with micromolar level of anti‐cryptospordial activities at concentrations nontoxic to the host cells (i.e. hexachlorphene, thimerosal, alexidine dihydrochloride, and ebselen with EC50  = 0.53, 1.77, 8.1 and 165 μM, respectively). The anti‐CpHK activity of the four existing drugs provided us new reagents for studying the enzyme properties of the parasite hexokinase.